Green synthesized silver nanoparticles from Garcinia imberti bourd and their impact on root canal pathogens and HepG2 cell lines. Issue 55 (10th July 2017) - Sri Ramkumar, S. R.; Sivakumar, N.; Selvakumar, G.; Selvankumar, T.; Sudhakar, C.; Ashokkumar, B.; Karthi, S.
Abstract : Nanoparticle biosynthesis using the extract of medicinal plants in a non-hazardous mode has gained wide attention for various applications in nanomedicine. Abstract : Nanoparticle biosynthesis using the extract of medicinal plants in a non-hazardous mode has gained wide attention for various applications in nanomedicine. This study aimed to synthesize silver nanoparticles (AgNPs) using the aqueous extract of the Garcinia imberti and to evaluate their antibacterial and cytotoxic activities. Structural characterization of synthesized AgNPs was carried out using UV-Vis spectrophotometry, scanning electron microscopy (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR). SEM showed the formation of particles with average sizes of 25 to 40 nm. Energy dispersive spectroscopy (EDS) was used to analyze the AgNPs within the energy range of 3–3.1 keV to detect the presence of silver. Also, the presence of the face centered solid cubic crystal structure of metallic silver was confirmed with X-ray diffraction (XRD). The functional groups of the biomolecules present in the aqueous extract of G. imberti and their interaction with AgNPs were identified through FT-IR analysis. The biosynthesized AgNPs exhibited antibacterial activity against root canal isolates of Staphylococcus sciuri S5, Enterococcus faecalis S9 and Enterococcus faecium S11. The green synthesized AgNPs showed no significant effects on HepG2 cell lines at 75 μg mL −1 . Thus, the biosynthesized AgNPs are found to have potential for nano-based drug delivery in future root canal treatment applications.